Energy and exergy analysis of wind power plant: A case study of Gharo, Pakistan - Tahir, Muhammad Faizan; Haoyong, Chen; Guangze, Han; Mehmood, Kashif (Frontiers in Energy Research, 2022)
Sustainable, inexhaustible, economical, and clean energy has become a vital prerequisite to replace fossil fuel sources for power production. In such a context, countries like Pakistan, which are heavily skewed towards fossil fuel-fired plants, are diverting attention to install more and more indigenous renewable energy sources projects such as solar-photovoltaic and wind turbine power plants. In order to harness the maximum energy of wind turbines, it is crucial to factually and precisely assess system performance, which is traditionally inferred by energy analysis (first law analysis). Nevertheless, this analysis only computes the nominal power generation output and ignores the effect of meteorological variables that can lead to some serious errors during the energy planning phase. Consequently, this case study presents both the energy and exergy analysis of a wind farm located in Gharo town of Thatta District along the coastline of the Indus Delta. Energy analysis is carried out to quantify energy efficiency, while exergy analysis computes exergy efficiency by taking into account the effect of pressure, temperature, and wind speed. Comparisons of both efficiencies are provided, and the result substantiates that exergy efficiency turns out to be lower than energy efficiency. However, exergy is a more viable index due to the inclusion of exergy destruction, and in comparison to the energy indicator, it presents the actual performance of a thermodynamic system. The monthly energy and exergy efficiency of the general electric wind turbines are maximum in July having values of 0.5 and 0.41, respectively.